Carte de la Baye de Canadas, de la Rivière de Kebec, du banc de Terre-neuve et autres havres rades et batures où se fait d'ordinaire la pêche des morûes - Le Cordier, Simon (Havre de Grace, 1696)
Black and white. Compass rose with rhumb lines. Decorative title and note cartouches. Depths shown by soundings. Bar scale in French leagues. Inset (top left) shows the upper St. Lawrence as far as Quebec City. -- Ancillary map: Grand Banc de Terre Neuve. Includes depth soundings, compass rose, and indications of the presence of sea creatures, with legend (in the center cartouche, placed over Newfoundland). CNS map no. 337.